PENGUATAN INTEGRITAS MORAL BANGSA DENGAN PENDEKATAN PERINTAH DAN LARANGAN DALAM PANDANGAN HUKUM ISLAM - Tono, Sidik (Al-Mawarid Jurnal Hukum Islam, 2012)
This articlewilldescribethe functionsofcommand and prohibition inperspective ofIslamiclaw, especially its function instrengtheningthe nationâsmoralintegrity. In guarding theobservanceandobedience for God, He established thecommand to doneand prohibition to be abandoned. For obedience peoplewhocarry outorderswill be given happinessinthis world and heavenin thehereafter. On the contrary, people whoviolatethe banwill bepunishedbymiseryandhellin thehereafter. Commandsand prohibitionsinthiscase are used as a toolormediumfor Godtoeducatepeople or human being andstrengthen thehuman charactertobegood and better servantsin this world whoare ableto runall thecommandsof Godand away from theban. So Commands and Bans became guide of human being in action and doing anything in this world. Keywords:Integritas, Moral Bangsa, Perintah dan Larangan